Direct certification of a class of quantum simulations. (9th February 2017) - Hangleiter, D; Kliesch, M; Schwarz, M; Eisert, J
Abstract: One of the main challenges in the field of quantum simulation and computation is to identify ways to certify the correct functioning of a device when a classical efficient simulation is not available. Important cases are situations in which one cannot classically calculate local expectation values of state preparations efficiently. In this work, we develop weak-membership formulations of the certification of ground state preparations. We provide a non-interactive protocol for certifying ground states of frustration-free Hamiltonians based on simple energy measurements of local Hamiltonian terms. This certification protocol can be applied to classically intractable analog quantum simulations: For example, using Feynman-Kitaev Hamiltonians, one can encode universal quantum computation in such ground states. Moreover, our certification protocol is applicable to ground state encodings of IQP circuits aiming at the demonstration of quantum supremacy. These can be certified efficiently when the error is polynomially bounded.